2011
DOI: 10.1002/eat.20914
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic alliance in the early part of cognitive‐behavioral therapy for the eating disorders

Abstract: Objective: This study examined the strength of the therapeutic alliance in the early stages of cognitive-behavioral therapy (CBT) for the eating disorders, and whether the strength of that alliance is associated with early eating characteristics, comorbid Axis 1 and 2 features.Method: Forty-four eating-disordered patients completed measures of eating and Axis 1 and 2 characteristics at the start of therapy, and measures of the therapeutic alliance and eating characteristics at the sixth session of CBT.Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 32 publications
3
38
0
1
Order By: Relevance
“…However, it is important to note that the eating-disordered patients of CBT clinicians rate the working alliance relative positively (Waller, Evans & Stringer, 2012), and that the alliance might be driven by behavioural change rather than vice versa (Brown, Mountford & Waller, 2013), as found in CBT for other disorders (e.g., Tang & DeRubeis, 1999 However, it is also necessary to attend to how clinicians feel about delivering these aspects of therapy. As such, supervision could usefully provide a safe space for discussion of the process of therapy in combination with the development of technical competence, so that those aspects of treatment that might be more anxiety-provoking can be regularly discussed.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that the eating-disordered patients of CBT clinicians rate the working alliance relative positively (Waller, Evans & Stringer, 2012), and that the alliance might be driven by behavioural change rather than vice versa (Brown, Mountford & Waller, 2013), as found in CBT for other disorders (e.g., Tang & DeRubeis, 1999 However, it is also necessary to attend to how clinicians feel about delivering these aspects of therapy. As such, supervision could usefully provide a safe space for discussion of the process of therapy in combination with the development of technical competence, so that those aspects of treatment that might be more anxiety-provoking can be regularly discussed.…”
Section: Discussionmentioning
confidence: 99%
“…However, multiple studies have shown alliance to be relatively strong among patients with AN (Sly, Morgan, Mountford, & Lacey, 2013;Waller, et al, 2012). In fact, Antoniou and Cooper's qualitative review of the relationship between alliance and outcome in EDs (2013) suggested that the alliance strongly predicted outcome for patients with AN, whereas findings for BN, binge eating disorder (BED), and subthreshold eating disorders were mixed.…”
Section: Patient Diagnosismentioning
confidence: 99%
“…In a large RCT, stronger early (session 4) and mid-treatment (session 12) alliance was associated with fewer purge episodes at the end of CBT for BN, after accounting for baseline purge frequency (Constantino et al, 2005). Other studies fail to find that alliance is associated with change in eating disorder symptoms (e.g., Brown, Mountford, & Waller, 2013;Loeb et al, 2005;Waller et al, 2012). In a clinical trial comparing interpersonal psychotherapy (IPT) and CBT for BN, alliance at sessions 6, 10, or 18 failed to predict post-treatment purge frequency in either treatment condition, after accounting for baseline purge frequency (Loeb et al, 2005).…”
mentioning
confidence: 97%
“…Yet a prevailing view is that treatment outcome is related to individual therapist differences over and above therapeutic approach (e.g., Luborsky et al, 1986;Messer & Wampold, 2002) and that manual-based treatment approaches are less caring, less intuitive, less authentic, and even inappropriate for 'real-world clients' (Addis & Krasnow, 2000). Empirical research provides no evidence that therapeutic alliance is adversely affected by implementing manual-based treatments for BN, with patients rating the alliance favourably in randomised controlled trials (RCTs;Loeb et al, 2005) and naturalistic clinic settings (Waller, Evans, & Stringer, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation